Utilization of Power Point-Based Digital Technology in Improving Early Childhood Language Development - Kartika Kurniasih; Mutiara Febianti; Nina Desywati Simbolon; Sere Virgin; Theresia Sidauruk (PT. Global Research Collaboration, 2023)
This research aims to determine and improve the language development of early childhood. So, through this observation, researchers created PowerPoint as a use of digital technology to support learning activities with the hope that through this activity it can help teachers in delivering learning material and to improve children's language development. This research uses a literature study method with a qualitative research approach. Secondary data obtained online is then compiled, analyzed and then concluded. Learning is often centered only on the teacher and sometimes children find it difficult to concentrate while learning is taking place, this is what causes a lack of language development in children. So this research aims to find out and improve children's language development through PowerPoint as the use of digital technology to support learning.